Body composition and hemodynamic changes in patients with special needs - Tsukamoto, Masanori (J Dent Anesth Pain Med, 2016)
BACKGROUND: Some patients with special needs exhibit intellectual disability, including deficits in cognitive skills and decreased quality of life. The purpose of this study was to retrospectively compare changes in body composition and hemodynamics during general anesthesia in patients with and without special needs. METHODS: The backgrounds of patients who underwent oral maxillofacial surgery under general anesthesia were recorded from medical records. Intracellular water (ICW), extracellular water (ECW), stroke volume variation (SVV), and heart rate (HR) were recorded for 3 h after the start of anesthesia. Categorical data were compared using an unpaired t-test, and a P-value of less than 0.05 was regarded as significant. Numerical data were compared using the Bonferroni correction, and a P-value of less than 0.0125 was regarded as significant. RESULTS: A total of 21 patients were included in the study: 10 patients without special needs (non-S-group) and 11 patients with special needs (S-group). There were no significant differences in patients' backgrounds, except with regard to height (P = 0.03). In both groups, ICW and ECW were maintained, although they were lower in the S-group compared to the non-S-group. SVV was maintained in both groups, although it was higher in the S-group than the non-S-group. HR was significantly lower in the S-group 1 h after induction of anesthesia (P < 0.003). CONCLUSIONS: Changes in hemodynamics due to body fluid imbalance should be monitored during general anesthesia, especially for patients with special needs.